2017
DOI: 10.1038/srep46180
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of the VanA-type VanS histidine kinase: an extended solution conformation and first evidence for interactions with vancomycin

Abstract: VanA-type resistance to glycopeptide antibiotics in clinical enterococci is regulated by the VanSARA two-component signal transduction system. The nature of the molecular ligand that is recognised by the VanSA sensory component has not hitherto been identified. Here we employ purified, intact and active VanSA membrane protein (henceforth referred to as VanS) in analytical ultracentrifugation experiments to study VanS oligomeric state and conformation in the absence and presence of vancomycin. A combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 51 publications
4
75
1
Order By: Relevance
“…Experimental evidence for this model has been provided in a study that used biophysical approaches such as analytical ultracentrifugation and near-UV circular dichroism (CD) to monitor the changes in oligomerization and conformation of detergent-solubilized VanS A in the presence of vancomycin. 51 Another study further supported this model demonstrating that vancomycin induced significant thermostability and conformational changes in purified VanS A, while other potential signals such as the peptidoglycan components Ala-D-γ-Glu-Lys-D-Ala-D-Ala, N-acetylmuramic acid or D-Ala-D-Ala had no such effect. 52 However, other studies contested this model, reporting the lack of a VanS A -vancomycin complex even at high concentrations of vancomycin and suggesting that the enzymatic activities of detergent or amphipol-solubilized VanS A are not altered in the presence of vancomycin.…”
Section: Vans Sensor Kinasementioning
confidence: 81%
See 1 more Smart Citation
“…Experimental evidence for this model has been provided in a study that used biophysical approaches such as analytical ultracentrifugation and near-UV circular dichroism (CD) to monitor the changes in oligomerization and conformation of detergent-solubilized VanS A in the presence of vancomycin. 51 Another study further supported this model demonstrating that vancomycin induced significant thermostability and conformational changes in purified VanS A, while other potential signals such as the peptidoglycan components Ala-D-γ-Glu-Lys-D-Ala-D-Ala, N-acetylmuramic acid or D-Ala-D-Ala had no such effect. 52 However, other studies contested this model, reporting the lack of a VanS A -vancomycin complex even at high concentrations of vancomycin and suggesting that the enzymatic activities of detergent or amphipol-solubilized VanS A are not altered in the presence of vancomycin.…”
Section: Vans Sensor Kinasementioning
confidence: 81%
“…Recognition of vancomycin would trigger VanS A dimerization, autophosphorylation, and transfer of the phosphoryl group to VanR A . Experimental evidence for this model has been provided in a study that used biophysical approaches such as analytical ultracentrifugation and near‐UV circular dichroism (CD) to monitor the changes in oligomerization and conformation of detergent‐solubilized VanS A in the presence of vancomycin . Another study further supported this model demonstrating that vancomycin induced significant thermostability and conformational changes in purified VanS A, while other potential signals such as the peptidoglycan components Ala‐ d ‐γ‐Glu‐Lys‐ d ‐Ala‐ d ‐Ala, N ‐acetylmuramic acid or d ‐Ala‐ d ‐Ala had no such effect .…”
Section: Vancomycin Resistance Mechanisms: Two Main Routes For Modifimentioning
confidence: 94%
“…However, it should also be borne in mind that, for most glycopeptide antibiotics studied to date [72][73][74] including vancomycin 66 , it has been shown that binding to depsipeptide targets is accompanied by formation of asymmetric, back-to-back homodimers of the glycopeptide in aqueous solution and that this is mediated by sugar-sugar recognition 75,76 . Although glycopeptide antibiotics are known to bind or interact with protein targets such as d-alanyl-d-alanine and VanS 4,6 , precipitation with another glycoprotein, heparin, has also been reported previously. However, this only appears to occur at relatively high concentrations of both components such as those used in intravenous lines (vancomycin at 1-5 mg/mL and heparin at 1-1000 Units/mL) [77][78][79][80] .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the variation of M w with loading concentration revealed dissociation constants in the range 25-75 µM, commensurate with a relatively weak association. That study 4 , alongside companion studies 6,7 , also demonstrated a weak interaction with the A-type bacterial VanS histidine protein kinase involved in the activation of vancomycin resistance, at least in aqueous solution.…”
mentioning
confidence: 84%
“…Circular dichroism (CD) (and synchrotron circular dichroism (SCD)) spectroscopy is widely used to study chiral molecules, in particular biomolecules in solution and in thin amorphous dry films. It is often used to elucidate secondary structural composition and to investigate tertiary structural conformational changes in biological monomeric, oligomeric and polymeric molecules including proteins and peptides (e.g., [1][2][3][4][5][6][7][8][9][10]), nucleic acids (e.g., [4][5][6]11]), carbohydrates and polysaccharides (e.g., [4,[12][13][14][15][16][17][18][19][20]). In the definition of CD, it is a chiroptical method that requires the molecule under study to possess optical activity (chirality).…”
Section: Introductionmentioning
confidence: 99%